THE STUDY OF TEACHING READING COMPREHENSION DURING ONLINE CLASS IN ENGLISH DEPARTMENT OF UNIVERSITY OF ISLAM MALANG: STUDENTS' PERCEPTION - Dina Ayu Siyah Rahmi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aimed to explore the students’ perception towards teachingonline reading comprehension which included students’ obstacles, class activities, and students’ perception towards their reading comprehension during online class. The subjects were four students of English Department of University of Islam Malang who experienced online reading class in 4th semester which had chosen through purposive sampling. Then, to obtain the data, the researcher conducted in-depth-interviews. The researcher found four main points of student perceptions. First, lecturer managed the class by utilizing WhatsApp feature, Zoom Meeting and Google Classroom apps. For the activity, students read and summarized some reading sources to be collected to the lecturer. Second, students faced the obstacles, such as how to use the technology and how to manage their time. Then, all of participants said that the lecturer way to manage and give the class activity was effective, they felt the improvement on their reading because of the activity. The last, students gave their perception about things that must be implemented in online reading class for getting better reading comprehension.Based on the findings, this study was conducted in limited scope and has a number of limitations. It will be better to add another instrument and get the lecturer’s point of view in the next study. The suggestions were addressed to lecturer to be more sensitive about the students need while doing class activities, such as additional information and feedback. The lecturer needs to add interactive and interesting activities to enhance students' motivation in online reading class.